Body Mass Index trajectories of Indigenous Australian children, and relation to screen-time, diet, and demographic factors - Dobbins, T; Banwell, Cathy; Thurber, Katherine; Neeman, T; Banks, Emily (My University, 2017)
Objective: Limited cross-sectional data indicate elevated overweight/obesity prevalence among Indigenous versus non-Indigenous Australian children. This study aims to quantify body mass index (BMI) trajectories among Indigenous Australian children aged 3-6 and 6-9 years and to identify factors associated with the development of overweight/obesity. Methods: Three-year BMI change was examined in up to 1,157 children in the national Longitudinal Study of Indigenous Children. BMI trajectories among children with normal baseline BMI (n = 907/1,157) were quantified using growth curve models. Results: Baseline prevalences of overweight/obesity were 12.1% and 25.4% among children of mean age 3 and 6 years, respectively. Of children with normal baseline BMI, 31.9% had overweight/obesity 3 years later; BMI increased more rapidly for younger versus older (difference: 0.59 kg/m2 /year; 95% CI: 0.50-0.69), female versus male (difference: 0.15 kg/m2 /year; 95% CI: 0.07-0.23), and Torres Strait Islander versus Aboriginal (difference: 0.36 kg/m2 /year; 95% CI: 0.17-0.55) children. Results were consistent with less rapid rates of BMI increase for children with lower sugar-sweetened beverage (including fruit juice) and high-fat food consumption. Children's BMI was lower in more disadvantaged areas. Conclusions: Overweight/obesity is common, and increases rapidly, in early childhood. Interventions are required to reduce the overweight/obesity prevalence among Indigenous Australian children in the first 3 years of life and to slow the rapid overweight/obesity onset from age 3 to 9 years.
Obesity
Keywords: Health and wellbeing; Health and wellbeing